MANUFACTURE OF HIGH-TEMPERATURE ELECTRIC HEATERS BASED ON THE SOLAR ENERGY - Kodirov, Bekzod (Журнал иностранных языков и лингвистики, 2023)
The role of solar energy as a natural energy source for the synthesis of electric heaters is discussed in this article. The work of famous scientists on the development of the field of using energy devices based on solar energy in heat supply systems is presented. In addition, you will get acquainted with the most popular and probably unfamiliar electric heaters, their types, and modes of operation. You will also learn about the process of making electric heaters imported to date based on solar energy. Where and why electric heaters are used, their functions, you will be able to use a local product that completely replaces the imported product.